Who Feels Credit Constrained in Europe? The Role of Social Capital. Issue 2 (30th August 2016) - Pereira, Maria C.; Coelho, Filipe; Lourenço, Óscar
Abstract : This paper analyzes the influence of social capital in consumers' perceptions of their borrowing constraints, which affect numerous financial decisions. Social capital is a multidimensional concept that concerns consumers' ability to obtain benefits from their engagement in social activities and social networks. To test the hypotheses, we rely on data from the European Social Survey. The results indicate that the four indicators of social capital (bonding capital, bridging capital, trust in people, and trust in institutions) are negatively associated with perceived borrowing constraints, and that some of these associations are moderated by income. The relationship of bonding capital with perceived borrowing constraints appears to be stronger than that of bridging capital, and trust in people reveals a stronger association with the outcome variable than trust in institutions. These results suggest several implications for practice and theory.